The Role of Economic Development in Strengthening the Democracy at the Grass Roots Level: An Assessment of the Issue in Theory and Practice - Sharma, Gunanidhi (Tribhuvan University Journal, 2010)
Not available. Key words: Economic Development; Democracy; Grass Roots Tribhuvan University Journal Vol. XIX, 1996 Page: 155-164 Uploaded Date: 24 Nov., 2010